Performance sensor analysis of HC-SR04 proximity sensor on distance measuring device with fuzzy logic method - Hirzii, M. Fakhrul; Pasaribu, Sutrisno Arianto; Sabila, Puji Chairu; Parlindungan, Mhd. Reivan (Journal of Computer Science and Research (JoCoSiR), 2023)
The HC-Sr04 ultrasonic sensor (proximity sensor) is a widely used ultrasonic sensor, in addition to its affordable price also because of its easy use and easy installation. Ultrasonic sensors are electronic devices whose ability can convert from electrical energy into mechanical energy in the form of ultrasonic sound waves. HC-SR04 sensor is one of the ultrasonic sensors that is often used to monitor the distance of objects (objects) with sensors. This sensor consists of a series of ultrasonic transmitters called transmitters and ultrasonic receivers called receivers. The distance that can be handled ranges from 2 cm to 400 cm, with a precision level of 0.3 cm. The detection angle that can be handled is no more than 15°. The required current is not more than 2mA and the required voltage is +5V. The number of pins is 4. In this study, the authors used the fuzzy logic method to help classify the level of distance received by the sensor. Fuzzy logic is used because this method is able to determine the classification results of the received values, according to what is needed by the distance measuring device with this ultrasonic sensor.